Persons With Schizophrenia Misread Hemingway: A New Approach to Study Theory of Mind in Schizophrenia - Fekete, Judit; Pótó, Zsuzsanna; Varga, Eszter; Csulak, Tímea; Zsélyi, Orsolya; Tényi, Tamás; Herold, Róbert (Frontiers in Psychiatry, 2020)
Introduction: Theory of Mind (ToM) is a key component of social cognition. Recently the Short Story Task (SST) was developed as a new measurement of ToM. SST uses a short story of Ernest Hemingway to assess ToM skills. SST proved to be a suitable tool, and sensitive to individual differences among healthy subjects. Our aim was to test SST to evaluate the ToM skills of patients with schizophrenia. Materials and methods: SST was used to assess ToM skills. After reading the short story “The End of Something” a structured interview was done with 14 questions. Spontaneous mental state reasoning, explicit mental state inference and comprehension of nonmental aspects of the story were evaluated. 47 patients with schizophrenia and 48 healthy controls were assessed and compared. Results: Patients with schizophrenia performed significantly more poorly in the explicit mental state inference questions. Ceiling effect was not detectable in explicit ToM scores. Patients made less spontaneous mental state references as well, although the occurrence of spontaneous mental state terms was infrequent in both groups. Patients were also less accurate in answering comprehension questions, but the difference was not significant after Bonferroni correction. Discussion: We found that our results lined up with the original findings on SST. The SST is a sensitive tool to explore the individual differences in ToM performance, especially in explicit mental state inferences, not only among healthy subjects, but also among patients with schizophrenia.